PENGARUH KUALITAS PRODUK, PROMOSI DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA ILSPROJECT DAN LITTLE MANGO STORE DENPASAR - Ni Wayan Chandra Tania; Ni Putu Nita Anggraini; Pande Ketut Ribek (EMAS, 2022)
Today, the level of competition in the business field is not only emphasized on the price aspect, but also involves other variables related to value in the customer shopping experience. For this reason, as business actors in each business category, they are required to be sensitive to any changes that occur and place an orientation to customer satisfaction as the main goal. This study aims to examine and obtain empirical evidence of the effect of product quality, promotion and electronic word of mouth on purchase satisfaction at Ilsproject and Little Manggo Store Denpasar. This research was conducted at Ilsproject and Little Manggo Store Denpasar using a sample of 97 respondents. The sampling technique used in this study was purposive sampling method. Data was collected through interviews and questionnaires. The data analysis technique used in this study was multiple linear regression analysis which was processed using the Statistical Package Social Science (SPSS) version 26. The results showed that product quality, promotion and electronic word of mouth had a positive and significant effect on purchasing decisions at Ilsproject and Little Manggo Store Denpasar, while. Things that must be improved are good relations between producers and consumers, paying more attention to product quality results, promotions, and it is hoped that companies will be able to increase the sense of belonging from consumers so that consumers can contribute to the company. Future research is expected not to rely on the factors in this study, namely product quality, promotion and electronic word of mouth in research, but can add other factors that might influence purchasing decisions.